2017
DOI: 10.1093/humrep/dex069
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of trophoblast differentiation and survival by low molecular weight heparin requires heparin-binding EGF-like growth factor

Abstract: This research was supported by grants from the National Institutes of Health (HD071408 and HL128628), the March of Dimes, and the W. K. Kellogg Foundation. There were no conflicts or competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…This was accompanied by an increase in PlGF levels in the conditioned media; while the mechanism has not been well-explored, heparin could potentially elevate PlGF release by promoting de novo synthesis, stimulating release of intracellular stores, or displacing cell-surface heparin-binding PlGF isoforms, such as PlGF-2 or PlGF-4. Previous investigators have also shown that LMWH enhances trophoblast differentiation and survival [28, 29] and promotes extravillous trophoblast invasion [30]. Collectively, these data support the hypothesis that LMWH favorably influences placental development and normalizes angiogenic protein release, which may subsequently alleviate the systemic endothelial dysfunction evident in women with preeclampsia.…”
Section: Discussionsupporting
confidence: 80%
“…This was accompanied by an increase in PlGF levels in the conditioned media; while the mechanism has not been well-explored, heparin could potentially elevate PlGF release by promoting de novo synthesis, stimulating release of intracellular stores, or displacing cell-surface heparin-binding PlGF isoforms, such as PlGF-2 or PlGF-4. Previous investigators have also shown that LMWH enhances trophoblast differentiation and survival [28, 29] and promotes extravillous trophoblast invasion [30]. Collectively, these data support the hypothesis that LMWH favorably influences placental development and normalizes angiogenic protein release, which may subsequently alleviate the systemic endothelial dysfunction evident in women with preeclampsia.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, Sildenafil citrate (Viagra) applied to H/R HTR-8/SVneo cells can promote cell survival, if in the presence of NO and cGMP [ 33 ]. Oxidative stress-induced apoptosis can also be attenuated by HBEGF treatment in first trimester placental explants, as well as on the HTR-8/SVneo cells [ 34 ]. In these cells, exposure to oxygen peroxide induced down-regulation of HLA-G expression, a trophoblast immunomodulatory molecule that facilitates implantation and placental development [ 21 ].…”
Section: Cellular Sources Of Oxidative Stress In the Human Placentmentioning
confidence: 99%
“…Enoxaparin‐treated EVT‐like cells also underwent integrin switching from α 6 β 4 to α 1 β 1 , which is associated with increased invasiveness. This heparin effect was dependent on heparin‐binding epidermal growth factor signaling . In healthy pregnant rats, LMWH reduced decidual expression of E‐cadherin, a cell adhesion molecule (CAM) whose level is elevated in pre‐eclamptic placentas and that is associated with reduced invasive phenotypes .…”
Section: Potential Non‐anticoagulant Mechanisms Of Heparin In Pre‐eclmentioning
confidence: 99%
“…In addition to stimulating proliferation, heparin also protects against apoptosis of trophoblasts by increasing expression of the antiapoptotic factor Bcl‐2 . Heparin‐binding epidermal growth factor is also important for this cell survival mechanism , the production of which is stimulated by LMWH treatment . These positive effects on placental development impact on overall function, as demonstrated by elevated secretion of human chorionic gonadotropin and PlGF from LMWH‐treated placental villous explants .…”
Section: Potential Non‐anticoagulant Mechanisms Of Heparin In Pre‐eclmentioning
confidence: 99%